74 DISTRIBUTION AND CORRELATES OF ARTERIAL COMPLIANCE MEASURES IN ASYMPTOMATIC YOUNG ADULTS: THE BOGALUSA HEART STUDY. (1st January 2005) - Bhuiyan, A. R.; Li, S.; Li, H.; Chen, W.; Srinivasan, S. R.; Berenson, G. S.
Abstract : Background: Impaired arterial compliance is an independent predictor of early vascular damage and related adverse cardiovascular (CV) outcome. However, information is scant on the distributions and correlates of measures of arterial pulsatile function in a community-based, biracial cohort of young adults. Methods: This study examined 800 black and white subjects (71% white, 43% male) aged 18-44 years enrolled in the Bogalusa Heart Study. In addition to traditional CV risk factor variables, pulsatile arterial function was assessed in terms of large artery (capacitive) compliance, small artery (oscillatory) compliance, systemic vascular resistance and vascular impedance by noninvasive radial artery pressure pulse contour analysis. Results: Blacks vs whites and females vs males had lower large and small artery compliances and higher systemic vascular resistance and vascular impedance (p < .001). Based on the significant associations noted in bivariate analyses, age, body surface area, BMI, mean arterial pressure, cardiac output (for small artery compliance, systemic vascular resistance, and vascular impedance only), LDL cholesterol (for small artery compliance only), triglycerides, HDL cholesterol (for large artery compliance and vascular impedance only), insulin (for large artery and small artery compliances and vascular impedance only), and glucose (for large artery compliance only) were included along with race and gender as independent variables in multivariate regression models. Mean arterial pressure, BMI, insulin and age were correlated inversely and body surface area positively with large artery compliance and accounted for 39.2% of the variance; mean arterial pressure, female gender, age and triglycerides inversely and cardiac output positively with small artery compliance and explained 56.4% of the variance; mean arterial pressure and age positively and cardiac output inversely with systemic vascular resistance and accounted for 91.4% of variance; and mean arterial pressure and BMI positively and cardiac output and body surface area inversely with vascular impedance and contributed to 37.6% of the variance. Conclusions: The observed deleterious impact of traditional CV risk factors on the arterial wall dynamics in asymptomatic young adults has important implications for preventive cardiology. Characterizing radial artery waveform morphology by a practical noninvasive device may be helpful for evaluation of early vascular damage in a high-risk young population group.